QueerCrip fashion in the twenty-first century: Sky Cubacub and the QueerCrip Dress Reform Movement. Issue 3 (1st December 2018) - Reddy-Best, Kelly L.; Goodin, Dana
Sky Cubacub, designer, artist and twenty-first century activist, based in Chicago, Illinois, creates garments and accessories for their fashion brand Rebirth Garments while critically considering gender, body size and ability, using the body and its expressions as a site of resistance and rebellion. This research is a case study of the life of Sky Cubacub and their work. We used the oral history method and triangulated information from the oral history with a material culture approach by analysing garments or apparel-related items produced by the designer; their self-produced zine/manifesto; and analysis of content on their social media accounts. Cubacub challenges ideas of visibility and ambivalence around the identities of queerness, fatness and disability. Through Cubacub's life story, design philosophy and business practices, these shifting and, most importantly, stigmatized and invisible identities can be expressed on an individualized basis in a celebratory fashion, leading into the twenty-first century as a hyperaware designer who is arguably a model for others looking to do the same.